PENGARUH TINGKAT KEPEDULIAN SOSIAL DAN KEMAMPUAN INTERAKSI SOSIAL SISWA TERHADAP PERILAKU BULLYING PADA SISWA - Anis Sayadi; Ahmad Baidowi (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2025)
Bullying behavior is a negative behavior that causes a person to feel uncomfortable and occur repeatedly. In this study, one factor of bullying behavior is the level of social concern and social interaction skills of the students. The research aims to: (1) analyze and describe the social care level of class V students at MI Malang Raya, (2) analyzing and describing the social interaction skills of class V students at MI Malang Raya. (3) Analyzing and describing the influence of Cheframonantonio's concern for bullying behavior, (4) analyzing and describing the influence of students ' social interaction skills on bullying behavior. The method in this study is a quantitative method of correlational type. The population in this study is V-grade students at MIN 2 Malang city, MI Maarif 02 Singosari, and MI Miftahul Ulum Batu. Samples were taken as many as 117 students using random sampling techniques. As for the data collection techniques using polls and documentation. Data analysis technique using multiple regression analysis, t-test, F test, coefficient of determining which is preceded by test assumption of normality test, Linieritas test, and multicollinearity test. The results in this study showed that: (1) The social care level of class V students amounted to 84% with a high category. (2) The social interaction capability of class V students amounted to 58.9% with a high category. (3) There is a partial and significant influence between the level of social concern on bullying behavior with a value of the calculated T 3.343 > 1.984 and the significance of 0.001 < 0.05. (4) There is a partial and significant influence between the ability of the social interaction of bullying behavior with the calculated T value 7.965 > 1.984 and the significance of 0.000 < 0.05. Keyword : Social Concern, Students’ Social Interaction , Bullying